Is there a synergy between artificial intelligence, Erasmus+ PEER-TRAIN training and MoodleCloud? - Anna, Grabowska (Magyar Gerontológia, 2023)
Artificial intelligence can be used in the teaching and training process to provide a personalized approach to each student. Erasmus+ PEER-TRAIN training focuses on developing the skills of teachers and trainers who work with youth and adults in the field of education and training.